FAKTOR DOMINAN PADA TEKANAN DARAH PENDERITA HIPERTENSI - Putri, Selly Marsela (JURNAL MEDIA KESEHATAN, 2017)
The lifestyle changes influence to dietary habit, less physical activity, smoking,stress, family’s background and eating foods habit in high natrium, low fiber, low potassiumand low calcium will bring the consequences of developing hypertension. The aim of thisresearch was to find the relation between the consumptions of fiber, natrium, potassium,calcium and physical activity with blood pressure of hypertension patients at Basuki Rahmadlocal medical center working area Bengkulu City on 2016. This research was survey analyticwith cross-sectional approachment. The sample was done by using simple random samplingtechnique. Then the data was analyzed in bivariet by using correlation regression and wasanalyzed through multivariate by using double linier regression. The result of this researchshowed the respondents consumption of fiber, natrium, potassium, calcium was under theaverage normal requirements and the physical activity of hypertension patients was in mildactivity category (p value < 0,05). The dominant factor of blood pressure relation in thisresearch was fiber consumption. It is needed to do socialization and nutrient consultation byusing leaflets about the food that contains high fiber, potassium and calcium and also lownatrium to hypertension patients so that the respondents can keep dietary habit and reduce bloodpressure.